A STUDY OF FACTORS INFLUENCING THE VALUE OF THE MAXIMUM DANGEROUS AMOUNT OF TRACK GAUGE - O. I. Bielorusov (Nauka ta progres transportu, 2007)
In the given publication it is proved that in calculations of maximum dangerous width of a rail track it is necessary to consider both plays and presence of tolerances at manufacturing the elements of rail fastenings.